Implementation of serious games for data privacy and protection awareness in Cybersecurity - Siti Normaziah, Ihsan; Tuty Asmawaty, Abd Kadir; Nurul Ishafira, Ismail; Yuan, Kerk Zhi; Jie, Yeow Song (Institute of Electrical and Electronics Engineers Inc., 2023)
Information security and privacy are big issues in today's digital world, and people should be aware of the risks that come with using their personal information online. There are many things that can be done to make people more aware of the importance of keeping personal information safe from attacks, such as an educational campaign, workshops and training sessions, public service announcements, and events in the community. Serious games, which are also called educational games, are a type of educational campaign activity that is meant to teach or train players about a certain subject or skill. They can play an important role in raising awareness of data privacy and information security by providing an engaging and interactive way for players to learn about these important topics. In this study, we suggest a game design architecture for protecting and keeping data private in cybersecurity. In order to validate the architecture, Datanion, a platform game, was created to educate the public on maintaining data privacy over the internet. This lack of awareness will have negative effects on mental health, private information, and computer equipment. Through these games, players can learn the basics of cybersecurity in a fun way, such as how to use strong passwords, recognise and avoid phishing websites, and how firewalls work. The advantage of playing these games is that they can help non-expert end users improve their knowledge and awareness of cybersecurity and also increase a player's motivation, engagement, and comprehension of cybersecurity knowledge.